Investigating the impact of the OOP-SOLVE application on the user’s behavior using the technology acceptance model in the programming course - Malik, Sohail Iqbal; Mathew, Roy; Tawafak, Ragad M.; Al-Farsi, Ghaliya; Al-Sideiri, Abir (Frontiers in Computer Science, 2025)
Introductory programming courses are considered difficult and challenging for students. They have to focus on and develop different skills related to problem-solving and programming domains concurrently. However, most programming courses spend more time teaching programming syntax. Therefore, this study developed and introduced an application, OOP-SOLVE, which focused on algorithmic thinking skills in the object-oriented programming (OOP) domain. The pseudo-code technique is used to create this application. Most of the teaching topics of the OOP course, such as classes, objects, constructors, inheritance, and polymorphism, are covered in this application. Moreover, the application presents each programming question in different sections such as class diagram, main class, test class, execution process, and output. A technology acceptance model (TAM) was used to investigate the acceptance of the OOP-SOLVE application in the OOP course. Moreover, the perceptions of the OOP course lecturers regarding the OOP-SOLVE application were collected by conducting a semi-structured interview. 224 students participated in the survey, and six lecturers participated in the interviews. Results show a positive impact of perceived ease of use, usefulness, and enjoyment on students’ attitudes toward their intention to use the application in the course. Lecturers also agreed that the application supported students in the OOP course. Moreover, it promotes students’ engagement and enhances collaboration and interaction among students in class activities. In addition to the solution of the given programming statement, the OOP-SOLVE application also presents the execution process of the program along with the output of each programming question. Lecturers also agreed that the application can be a supporting teaching tool in the OOP course.